Proteasomal activity‐based probes mark protein homeostasis in muscles. Issue 5 (3rd July 2017) - Raz, Vered; Raz, Yotam; Paniagua‐Soriano, Guillem; Roorda, Jacomina Cornelia; Olie, Cyriel; Riaz, Muhammad; Florea, Bogdan I.
Abstract: Background: Protein homeostasis, primarily regulated by the ubiquitin–proteasome system is crucial for proper function of cells. In tissues of post‐mitotic cells, the impaired ubiquitin–proteasome system is found in a wide range of neuromuscular disorders. Activity‐based probes (ABPs) measure proteasomal proteolytic subunits and can be used to report protein homeostasis. Despite the crucial role of the proteasome in neuromuscular pathologies, ABPs were not employed in muscle cells and tissues, and measurement of proteasomal activity was carried out in vitro using low‐throughput procedures. Methods: We screened six ABPs for specific application in muscle cell culture using high throughput call‐based imaging procedures. We then determined an in situ proteasomal activity in myofibers of muscle cryosections. Results: We demonstrate that LWA300, a pan‐reactive proteasomal probe, is most suitable to report proteasomal activity in muscle cells using cell‐based bio‐imaging. We found that proteasomal activity is two‐fold and three‐fold enhanced in fused muscle cell culture compared with non‐fused cells. Moreover, we found that proteasomal activity can discriminate between muscles. Across muscles, a relative higher proteasomal activity was found in hybrid myofibers whereas fast‐twitch myofibers displayed lower activity. Conclusions: Our study demonstrates that proteasomal activity differ between muscles and between myofiber types. We suggest that ABPs can be used to report disease progression and treatment efficacy.